Intelligent fault diagnostic model for rotating machinery - Muhammad, M.B. (IEEE Computer Society, 2018)
The aim of this paper is to present an intelligent fault diagnostic to assess the changes and detect malfunctions in rotating machinery using real-time data. The developed model interprets performance condition monitoring data and determines machine health status with the use of Artificial Neural Networks (ANN). The ANN networks were trained for principle performance parameters from which actual system performance can be predicted based on given set of input parameters. The validity of the proposed model was evaluated through a case study on twin-shaft 18700 kW industrial gas turbine engine to detect a fault happened in engine bell-mouth. The results showed the networks trained using Levenberg-Marquardt (LM) training function can achieve more accurate results compared to Bayesian regulation (BR) and scaled conjugate gradient (SCG) training functions. In addition, the results also showed that both power output parameter and the fuel flow rate can be effectively used to monitor the performance of gas turbine. Â© 2017 IEEE.